Controlled release biopolymers for enhancing the immune response - Castro, Guillermo Raúl (2007)
Controlled release of biologically active compounds in the context of drug and vaccine delivery is an important area of research with broad implications in many areas of medicine. In particular, the challenges of oral delivery are of specific interest to reduce the cost and potential health risks related to parenteral administration of pharmaceuticals and vaccine formulations. We discuss the biological activities of two biopolymers, β-glucans and emulsans, both of which offer significant potential for individual formulations related to drug impact, while in combination offer synergistic opportunities in terms of formulation and delivery. β-Glucans have been established as potent immunomodulatory and biologically active compounds with application in a wide range of disease systems. The emulsan family of biopolymers also has significant potential in vaccine and drug delivery based on recent studies. Each of these biopolymers offers exciting opportunities to modulate biological responses via control of chemistry and physical properties achieved during biosynthesis or postsynthesis modifications. When combined into a delivery system for controlled release, synergistic outcomes may be achieved that offer new and exciting opportunities as described in the present paper. These outcomes represent the combined improvements of solubility in physiological environments and immunomodulation due to the specific chemistry and structures involved. Overall, this approach provides a new direction in controlled release wherein the biomaterial carrier, in this case emulsan, and the drug, in this case β-glucan, play an active role both in biological activation as well as in delivery profiles.